Autogenous healing of fiber-reinforced reactive magnesia-based tensile strain-hardening composites - Qiu, Jishen (2021)
Reactive magnesia-based cement (RMC) is an emerging group of alternative binder to Portland cement. Recently, the first fiber-reinforced RMC-based strain-hardening composites (SHC) have been developed by the authors. The current work investigated the feasibility of the PC-free RMC-based SHC formulations to engage autogenous healing. Results showed that crack sealing and significant mechanical recovery can be realized through proper environmental conditioning. The presence of water is necessary to engage autogenous healing and elevated CO2 concentration leads to the formation of HMCs that can seal larger crack. However, ample supply of CO2 results in fast sealing of crack on the near surface region, which blocks the pathway for further carbonation and healing of interior region of cracks. Microstructure analysis reveals that the healing products are hydrated magnesium carbonates (HMCs) and different conditioning regimes lead to different types of HMCs as the healing products.